2011
DOI: 10.1103/physrevb.84.085426
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Si(100) at 5 K using qPlus frequency modulated atomic force microscopy: Role of defects and dynamics in the mechanical switching of atoms

Abstract: We use small-amplitude qPlus frequency modulated atomic force microscopy (FM-AFM), at 5 K, to investigate the atomic-scale mechanical stability of the Si(100) surface. By operating at zero applied bias the effect of tunneling electrons is eliminated, demonstrating that surface manipulation can be performed by solely mechanical means. Striking differences in surface response are observed between different regions of the surface, most likely due to variations in strain associated with the presence of surface def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…1). It has been shown that the structure of the rows may be locally manipulated by controlled tunnel-current injection [18], and we recently demonstrated that the buckling of the dimers can be toggled with atomic precision by direct application of mechanical force during NC-AFM [1920]. In this paper we present imaging and force spectroscopy of the Si(100) surface at 5 K by qPlus [21] NC-AFM at zero applied bias, and investigate the influence of different apex types on the qualitative image appearance, and quantitative short-range tip–sample force and dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…1). It has been shown that the structure of the rows may be locally manipulated by controlled tunnel-current injection [18], and we recently demonstrated that the buckling of the dimers can be toggled with atomic precision by direct application of mechanical force during NC-AFM [1920]. In this paper we present imaging and force spectroscopy of the Si(100) surface at 5 K by qPlus [21] NC-AFM at zero applied bias, and investigate the influence of different apex types on the qualitative image appearance, and quantitative short-range tip–sample force and dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most exciting applications of either of the techniques are related to their ability to perform nanomanipulation [3][4][5] . Both lateral [6][7][8] and vertical [9][10][11] manipulations have been used to build bottom-up nanostructures on surfaces. The latter manipulation, where the manipulated atom is either dropped to or extracted from the surface, normally results in a modification of the tip apex with the concomitant change of the image contrast.…”
mentioning
confidence: 99%
“…2 are simulated F ( z ) curves taken with the H3 (a) and D 1 (b) tips positioned above the up (green and black triangles) and down (red and blue circles) atoms of a surface Si(100) dimer. An in-depth description of the origins of the calculated force profile have been given elsewhere [8,13,42]. The key points, however, are summarised below.…”
Section: Resultsmentioning
confidence: 99%
“…Through understanding the interactions between the AFM tip and sample surface, the chemical interactions present in AFM images [15], manipulation experiments [610], and, more recently, submolecular investigations of planar molecules [1112], have been revealed. In covalent systems in particular, density functional theory (DFT) calculations have been extremely successful in explaining the fundamental interactions that underpin NC-AFM experiments [23 1316]. Moreover, atomistic simulations remain essential to many current studies in covalent [1719] and ionic [2021] systems because of the inherent difficulties in determining the tip apex structure from purely experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation